Rapid Detection of Klebsiella pneumoniae Carrying Virulence Gene rmpA2 by Recombinase Polymerase Amplification Combined With Lateral Flow Strips - Li, Na; Wang, Lei; Wang, Fang; Chen, Huimin; Tao, Shuan; Zhu, Qing; Liu, Liping; Liang, Wei; Ma, Fang (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract: Highly virulent Klebsiella pneumoniae often causes invasive infections with high morbidity and mortality rates, posing an immense clinical challenge. Rapid and accurate detection of pathogenic bacteria is of great significance for treatment and preventive control. Conventional detection by polymerase chain reaction (PCR) is limited by a dependence on laboratory equipment and professional staff. Recombinase polymerase amplification (RPA) combined with a lateral flow strip (LFS) can rapidly amplify and visualize target genes in a short period of time. The aim of this study was to develop an RPA-LFS technique for detection of the K. pneumoniae virulence gene rmpA2. Primers were designed against conserved sequences specific to the virulence gene, and primer probe design was optimized by introducing base mismatches to obtain a specific and sensitive primer-probe combination for clinical detection. We tested 65 actual samples collected from the clinic to evaluate the performance of the newly established RPA-LFS system in comparison with the conventional PCR method. The RPA-LFS assay was performed at for 30 min a constant temperature of 37 °C, and results could be observed without instrumentation. The system could specifically identify highly virulent K. pneumoniae carrying the virulence gene rmpA2 with a minimum detection limit of 10−1 ng/μL and 10 copies/μL. For the 65 clinical samples tested, RPA-LFS assay results were in complete agreement with the PCR results. The RPA-LFS assay provides a rapid, accurate, and simple method for identification of highly virulent K. pneumoniae carrying rmpA2.